A-55 Neuropsychological Findings Associated with Progressive Lesion Development in Cerebral Cavernous Malformation Secondary to PDCD10 Mutation. (30th August 2021) - Phillips, Matthew; Wisinger, Amanda; Fink, Joseph
Abstract: Objective: A rare mutation in the PDCD10 gene causes cerebral cavernous malformations, which can result in multiple brain hemorrhages and hundreds of lesions. Up to 50% of individuals with the PDCD10 mutation remain symptom-free throughout their lives; however, others can suffer from seizures or focal neurologic deficits. Participant: A 67-year-old Caucasian male presented for a neuropsychological re-evaluation (2020) following a progressive decline in his memory and attention dating back 20 years. A baseline neuropsychological evaluation was obtained 7 years ago. Relevant medical history included a 5 mm left falcine meningioma, epilepsy, obstructive sleep apnea, hypertension, and type II diabetes. Neuroimaging revealed over 250 scattered lesions that had advanced over the past 7 years, particularly in the paramedian pontine reticular formation, left inferior cerebellum, and right middle frontal gyrus. Results: His neurocognitive profile was marked by mild impairments in immediate verbal memory. The remainder of his cognitive profile was average. Compared to his 2013 evaluation, he showed only a minimal decline in verbal memory, but he showed slight improvements in the domains of executive functioning, visuospatial abilities, and language. Conclusion: Despite the marked progression of lesions documented on current neuroimaging, aside from immediate verbal memory problems the patient's neurocognitive functioning was relatively well-preserved. He even exhibited minor improvements within several domains. Given the patient's current neurocognitive status, this case illustrates the importance of comprehensive neuropsychological testing in cases that would appear more severe based on neuroimaging data alone. Relatedly, progression of neuropathological disease burden on neuroimaging is not necessarily accompanied by consistent progression of neuropsychological dysfunction.